The Effect Of Red Bean Flour Substitution On The Quality Of Putu Ayu Cake - Husna, Ainil; Syarif, Wirnelis (Universitas Negeri Padang, 2022)
This research is motivated by the lack of utilization of local ingredients such as red bean flour. This study aims to analyze the effect of substitution of red bean flour by 20%, 40% and 60% on the quality of the shape, color, aroma, texture and taste of putu ayu cake. This type of research is pure experiment, the object of this research is Putu Ayu. The variables of this study include independent variables with 4 factors, namely X0 (control), X1 (substitution of red bean flour 20%), X2 (substitution of red bean flour 40%), X3 (substitution of red bean flour 60%). The dependent variable is the quality of the putu ayu cake. The type of data is primary data sourced from 3 panelists who answered the organoleptic test format. The data obtained were analyzed using statistical analysis (ANAVA), if Fcount > Ftable, then continued with Duncan's test. The results of this study indicate that there is a significant effect on the substitution of red bean flour as much as 20%, 40% and 60% on the color quality (green red spots on the top of the putu ayu cake) Fcount > from Ftable (88.42 > 4.75) , texture (expanded) Fcount > from Ftable (46.67 > 4.75), while the quality of the jagged round shape, neat shape, white color on the top of the putu ayu cake, fragrant aroma, texture (soft), texture (porous) and sweetness has no significant effect because Fcount < from Ftable.